2004
DOI: 10.1103/physrevb.70.180501
|View full text |Cite
|
Sign up to set email alerts
|

Reading out the state inductively and microwave spectroscopy of an interferometer-type charge qubit

Abstract: We implemented experimentally an interferometer-type charge qubit consisting of a single-Cooper-pair transistor closed by a superconducting loop that is in flip-chip configuration inductively coupled to a radiofrequency tank circuit. The tank permits us to readout the qubit state, acting as an inductance measuring apparatus. By applying continuous microwave power to the quantum device, we observed inductance alterations caused by redistributions of the energy-level populations. From the measured data we extrac… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
35
0

Year Published

2005
2005
2018
2018

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 41 publications
(37 citation statements)
references
References 14 publications
(18 reference statements)
2
35
0
Order By: Relevance
“…In particular in a closely related experiment, the level separation of a split Cooper pair box coupled inductively to a low frequency, moderate Q tank circuit has been determined spectroscopically [15]. The width and the saturation level of the spectroscopic lines discussed above depend sensitively on the power P s of the spectroscopic drive.…”
mentioning
confidence: 99%
“…In particular in a closely related experiment, the level separation of a split Cooper pair box coupled inductively to a low frequency, moderate Q tank circuit has been determined spectroscopically [15]. The width and the saturation level of the spectroscopic lines discussed above depend sensitively on the power P s of the spectroscopic drive.…”
mentioning
confidence: 99%
“…Equation (18) for the voltage V coincides with the nonlinear equation (1) for the variable x with obvious change of the notations.…”
Section: Inductive Coupling With Lcr Resonator Parametric Inductancementioning
confidence: 99%
“…For characterization and controlling the states of superconducting qubits the one-photon spectroscopy was done by using relatively weak driving [11][12][13][14][15][16][17][18]. Matching of the ground and higher states with the one-photon energy was exploited to probe the upper levels of the Josephson-junction circuits [19][20][21][22][23][24][25][26].…”
Section: Introductionmentioning
confidence: 99%
“…reflecting vortex states with a high degree of superconducting phase coherence, the deep minimum at f = 1/2 points to a state in which the phase coherence is strongly suppressed. More recently, it was realized that JJAs can be also used as quantum channels to transfer quantum information between distant sites (Ioffe et al 2002, Born et al 2004, Zorin 2004 Many authors have used a parallelism between the magnetic properties of 2D-JJA and granular high-temperature superconductors (HTS) to study some controversial features of HTS. It has been shown that granular superconductors can be considered as a collection of superconducting grains embedded in a weakly superconducting -or even normal -matrix.…”
Section: Introductionmentioning
confidence: 99%